Avaliação dos aspectos anatomopatológicos da infecção natural por Eimeria Stiedai (Lindemann, 1865) Kisskalt e Hart, 1907 (Apicomplexa: Eimeriidae) em coelhos de criações rústicas(oryctolagus cuniculus) - Silva, Maria Eduarda Monteiro (2010)
This study aimed to investigate the frequency of liver eimeriosis, evaluate and describe the pathology of liver injury observed in various stages of development caused by E. stiedae rustic creations in rabbits naturally infected as well as establish the relationship between liver weight / carcass originated in the mountainous region Fluminense, RJ. We collected livers, gall bladders and faeces of 97 rabbits coming from rustic creations. The fecal samples were collected directly from the intestine and placed in a solution of potassium dichromate (K2Cr4O7) 2.5% (v / v), where they were kept between 23 and 28 ° C for 10 days for this to happen sporulation of oocysts and subsequent identification of these based on morphology and characterization of internal structures such as residual body, micropyle. In the livers, were evaluated macroscopic lesions, and were later made estiraços for the direct observation of oocysts, after preparation of the material. The contents of the gall bladder was collected with the aid of a 5-ml syringe and needle 25x0, 7 mm, for observation of sporulated oocysts not. For histopathological evaluation, representative samples were collected from livers that had lesions were packed in 10% buffered formalin, processed by routine technique and stained with hematoxylin-eosin, Masson's trichrome and PAS - Periodic Acid Schiff (Behmer et al. 1976 ). According to morphometric analysis of oocysts found in 18 animals (18.6%) belonged to the species E. stiedae. On the macroscopic lesions, the nodules were found positive for estiraços of 28 animals (27.4%), showing immature oocysts, as well as analysis of bile contents in 30 animals (29.4%). In relation to histopathology, fibrosis and intraluminal papillary projections were observed in all 43 animals (100%). It was also observed, stratification of ductal epithelium and mass of oocysts in the midst of an amorphous material, both promoting cholestasis in 15 animals (34.9%). Were no areas of hyperplasia, 25 animals (58.1%) and endogenous forms, in 3 animals (2.94%), in various stages of development by promoting epithelial destruction. Regarding the correlation between liver weight and carcass weight between the negative animals and infected animals were not statistically different with p <0.05. The investigation of coccidiosis by histopathological and parasitological analysis contributes to a better understanding of the pathogenesis of the agent and the development of appropriate management of keeping rabbits